Synthesis of bismuth oxychloride nanoparticles via co-precipitation method: Evaluation of photocatalytic activity. (2022) - Puttaraju, T.D.; Shashank, M.; Raja Naika, H.; Nagaraju, G.; Manjunatha, M.
Abstract: Bismuth oxychloride (BiOCl) nanoparticles were synthesized via chemical co-precipitation process at room temperature. The structural, optical and morphological features of synthesized BiOCl nanoparticles were characterized by using different analytical techniques such as XRD, UV-DRS, Raman and SEM. The XRD pattern of BiOCl NPs shows tetragonal phase having on average crystalline size was found to be 21 nm. The UV-DRS spectrum of BiOCl NPs exhibiting the energy band gap of 3.5 eV. The Raman spectroscopy was used to identify the characteristic A1g and Eg vibrational normal modes of BiOCl NPs. SEM micrograph of BiOCl NPs reveals the agglomeration of the particles with effect of reducing agent. Furthermore, the photocatalytic degradation of methylene blue dye using BiOCl NPs under UV light is investigated and found to be effective. The synthesis of BiOCl nanoparticles is very simple, inexpensive, and environmentally friendly and it's exhibiting the possibility of finding novel properties.